Website Human Resource Information System Dengan Fitur Pengukuran Efektivitas Kinerja Karyawan Pada PT. Deus Digital Transformasi Universal - Alvin Putra Wong; Alexander Setiawan; Lily Puspa Dewi (Universitas Kristen Petra, 2022)
PT. Deus Digital Transformasi Universal is a service company that focuses on website creation, social media management, and client product marketing. So far, the management of human resources is still mostly done manually, so it is very possible for recording errors or other errors that make the data inaccurate. PT. Deus Digital Transformasi Universal also plans to open several branches outside the Surabaya area which causes the company's need for a Human Resources Information System to be very strong and cannot be avoided anymore. HRIS is equipped with a decision support feature using the Analytical Hierarchy Process method that can display suggestions and actions for evaluating employee performance results. In this study, an HRIS was designed which has several modules, namely the Master module, recruitment module, project module, violation module, daily work module, performance module, and payroll module. To support decisions the system uses the Analytical Hierarchy Process used in the calculation process, and ranking of employee performance. The system is made based on a website using the laravel PHP framework, javascript, HTML, and MySQL database. The result of this research is a system that can help HRD in all matters of human resource management, and help company directors to be able to unify the work of employees, and their performance in real-time, and objectively.